Restrukturisasi Kredit dalam Perspektif Hukum Perbankan: Dampak terhadap Hubungan Kontraktual antara Bank dan Nasabah - Raisa Agnia; Sabili Casba Ar-Rusd; Gipal Herta Wijaya (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study examines credit restructuring from the perspective of banking law, with particular attention to its impact on the contractual relationship between banks and customers. Credit restructuring is conceptualized as a legal mechanism designed to preserve the continuity of credit agreements when payment difficulties arise, while maintaining the rights and obligations of the parties involved. The research adopts a normative juridical approach through an analysis of statutory regulations, legal doctrines, and the practical implementation of credit restructuring within the Indonesian banking system. The findings demonstrate that credit restructuring represents the application of the principles of prudence, good faith, and the balance of interests embedded in banking contract law. Amendments to credit terms through restructuring generate legal implications for the contractual positions of both parties, yet remain within the framework of legal certainty when grounded in mutual consent and prevailing regulations. From a legal protection standpoint, credit restructuring affords safeguards to customers against excessive exposure to default risks while simultaneously securing the legitimate interests of banks as creditors. Accordingly, credit restructuring plays a strategic role in sustaining legal stability and fostering trust within the banking sector.